The Presence of House Dust Mites in Residences and Classrooms of Students with Allergic Rhinitis - Suri Dwi Lesmana; Harianto Harianto; Reyza Octarient (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
Allergy is still a health problem in Indonesia. One of the manifestations of allergies is allergic rhinitis. Many factors can trigger the recurrence of rhinitis, including exposure to house dust mites. This study aims to identify the population of house dust mites in the classrooms and student residences. This study was participated by 74 FK UNRI students with allergic rhinitis. The samples included dust collected from residences and classrooms consisting of four large classrooms, three small classrooms, four laboratories, two examination rooms, 12 skills lab rooms, and 15 tutorial rooms. Detection of dust was performed using the direct method. The results showed that no classroom (0%) was found with house dust mites. However, there were 37.8% of residences were positive. Based on the result, it can be concluded that the high population of house dust mites in the students’ residences becomes an essential factor as a chronic stressor for allergic rhinitis.